An Aphid Effector Targets Trafficking Protein VPS52 in a Host-Specific Manner to Promote Virulence - Rodriguez, Patricia A.; Escudero-Martinez, Carmen; Bos, Jorunn I.B. (Plant physiology (Bethesda), 2017)
Plant- and animal-feeding insects secrete saliva inside their hosts, containing effectors, which may promote nutrient release and suppress immunity. Although for plant pathogenic microbes it is well established that effectors target host proteins to modulate host cell processes and promote disease, the host cell targets of herbivorous insects remain elusive. Here, we show that the existing plant pathogenic microbe effector paradigm can be extended to herbivorous insects in that effector-target interactions inside host cells modify critical host processes to promote plant susceptibility. We showed that the effector Mp1 from Myzus persicae associates with the host Vacuolar Protein Sorting Associated Protein52 (VPS52). Using natural variants, we provide a strong link between effector virulence activity and association with VPS52, and show that the association is highly specific to M. persicae-host interactions. Also, coexpression of Mp1, but not Mp1-like variants, specifically with host VPS52s resulted in effector relocalization to vesicle-like structures that associate with prevacuolar compartments. We show that high VPS52 levels negatively impact virulence, and that aphids are able to reduce VPS52 levels during infestation, indicating that VPS52 is an important virulence target. Our work is an important step forward in understanding, at the molecular level, how a major agricultural pest promotes susceptibility during infestation of crop plants. We give evidence that an herbivorous insect employs effectors that interact with host proteins as part of an effective virulence strategy, and that these effectors likely function in a species-specific manner.